Growing practices and the use of potentially harmful chemical additives among a sample of small-scale cannabis growers in three countries. (1st November 2018) - Lenton, Simon; Frank, Vibeke A.; Barratt, Monica J.; Potter, Gary R.; Decorte, Tom
Highlights: 44% of our 3 country sample of 1722 cannabis growers used any chemicals. Hydroponic growers were 12x more likely to use chemicals than natural growers. Poor product labelling made it impossible to determine constituents. Lack of product regulations put cannabis growers and users at risk. Abstract: Background: With the growth of legal cannabis markets there has been recognition of the adverse impacts of certain cannabis growing practices, notably, use of harmful chemicals. A major concern has been the use of Plant Growth Regulators (PGRs) which limit plant size and stimulate bud production. These chemicals, many of which have been banned from food crops, have been found unlisted in cannabis growing nutrients sold online or in hydroponic stores. This study describes the cannabis growing practices used by small-scale recreational cannabis growers and specifically their self-reported use of chemicals. Methods: Web survey data from 1722 current and recent cannabis growers in Australia, Denmark, and the UK, who were asked about their cannabis growing practices, including the use of fertilizers and supplements. Results: Overall 44% of the sample reported using any chemical fertilizers, supplements or insecticides. Logistic regression indicated that the unique predictor of the use of chemicals was growing hydroponically. Conclusion: Problems associated with product labeling and uncertainty regarding product constituents made it difficult for growers and the researchers to determine which products likely contained PGRs or other harmful chemicals. There is a need for further research to analyze constituents of chemical products marketed to cannabis growers.